THE GENERA GLYCYMERIS, AEQUIPECTEN AND ARCTICA , AND ASSOCIATED MOLLUSK FAUNA OF THE LOWER PLEISTOCENE ARDA RIVER SECTION (NORTHERN ITALY) - CRIPPA, GAIA; RAINERI, GIANLUCA (Milano University Press, 2015)
The Lower Pleistocene marine succession of the Arda River, cropping out at Castell'Arquato (Northern Italy), is well exposed, continue and richly fossiliferous. Itconsists of sandstones, siltstones and claystones and it is topped by continental conglomerates which indicate a major sea level drop. In the present paper Glycymeris glycymeris, Glycymeris inflata, Glycymeris insubrica, Aequipecten scabrella, Aequipecten opercularis and Arctica islandica are described and revised. In addition, the associated fauna is illustrated, and its biostratigraphic and palaeoclimatic significance is analyzed. This study points out that: 1) the fauna has a high biodiversity, comprising 159 taxa; bivalves are dominant, followed by gastropods, corals, serpulids, brachiopods, echinoids, arthropods (e.g. barnacles), bryozoans and scaphopods; 2) The last occurrences of the bivalves Aequipecten scabrella , Glycymeris inflata and Chama placentina , the first occurrence of Arctica islandica and the last occurrences of the gastropods Turritella tricarinata pliorecens and Nassarius prysmaticus suggest a late Gelasian-Calabrian age (Early Pleistocene) for the investigated marine succession; 3) the occurrence of boreal guests, such as Arctica islandica, Pseudamussium peslutrae and possibly Mytilus edulis, testify to a climatic change with a shift from warm to cold seawater temperatures.